HLA‐A, HLA‐B and HLA‐DRB1 allele and haplotype diversity among volunteer bone marrow donors from Croatia. (25th April 2014) - Grubic, Z.; Burek Kamenaric, M.; Mikulic, M.; Stingl Jankovic, K.; Maskalan, M.; Zunec, R.
Summary The determination of human leucocyte antigen (HLA)‐A, HLA‐B and HLA‐DRB1 alleles in the routine procedure of a volunteer hematopoietic stem cell (HSC) donor's registration in the Croatian Bone Marrow Donor Registry (CBMDR) is performed to enhance the odds of finding a suitable HLA compatible donor for patients in need of a HSC transplantation worldwide. However, besides its original purpose, it also provides valuable information about the HLA polymorphism among Croats. The aim of the present study was to analyse the HLA allele and haplotype frequencies in a sample of 4000 donors from CBMDR. The distribution of HLA‐A, HLA‐B and HLA‐DRB1 alleles did not demonstrate significant differences from the data reported for other European populations. The higher frequency of B*40:02 allele in comparison with B*40:01 and DRB1*11:04 in comparison with DRB1*11:01 is interesting because it represents a difference in comparison with the Western and Northern European populations which are a main source of donors for Croatian patients. The haplotype frequencies show a greater variation and difference in comparison with data from other registries and populations; however, due to a lack of high‐resolution haplotype data, comparison was possible only with a very limited number of other populations.